Post Ambulatory Discharge Follow-up Using Automated Text Messaging. - Leconte, David; Beloeil, Hélène; Dreano, Thierry; Ecoffey, Claude (Journal of Medical Systems, 2019)
Ambulatory surgery has grown to be the most common procedure in developed countries. Efficient quality of care and safety often require calling patient at day one after outpatient surgery to check patient's recovery and search for complications. This increasing flow in same day surgery centres motivates the use of automatic systems to contact patients. The overall objective of this study was to evaluate automated software sending text messages (TM) to patients at day 1 after ambulatory surgery compared to classical phone calls. This prospective study took place in Rennes Teaching Hospital, France, from June 1st, 2015 to December 15th, 2016. All patients owning a mobile phone were included, adults and children by means of their parents. The primary end point was the rate of successfully contacted patients, compared to usual phone calls in 2014. In cases of no response or an abnormal response, an automatic alert was sent to the ambulatory unit. Within the 7246 patients included, response rate to TM was significantly higher than response to phone calls in 2014 (87% vs 57%, respectively p < 0.0001). Most patients (85%) responded in less than 60 min. The TM algorithm detected 36% alerts (12% for lack of response to TM and 24% for TM's content). The total of reached patients' rate with TM and then phone call after an alert was 90%. Post ambulatory discharge follow-up using automated TM was successfully and easily experienced as more patients were contacted.